Life table parameters of red scale insect Aonidiella aurantii Maskell,1879 on Lemon fruits in the laboratory - نجمه, علا; علي رمضان,; نبيل أبو كف ,; محمد خير محمد, (Latakia University Journal -Biological Sciences Series, 2024)
The red scale insect Aonidiella aurantii (Maskell, 1879) (Hemiptera: Diaspididae), is a worldwide pest, and one of the most important pests infesting citrus in Syria. life table parameters were studied in the general insect laboratory at the Faculty of Agricultural Engineering at Tishreen University, under conditions of temperature 25±1°C, relative humidity 65±5%, and lighting (16L:8D), using the TWOSEX-MSChart program. The results showed that the Intrinsic rate of increase (r) 0.06±0.007 female/female/day, Finite rate of increase (λ) 1.06±0.01day, Net reproductive rate (R0) 30.51±9.56 female/female/generation, Generation time (T) 54.69±0.86 days, Gross reproduction rate (GRR) 206.75±24.98 individuals/offspring, Doubling time (DT) 11.08 days. Pre-oviposition period of female adult 6.22±0.4 days, total pre-oviposition period of female adult 38.22±0.91 days, Fecundity (F) 271.22±10.39 eggs/female. The results also showed that mean longevity of female 66.61±2.8 days, while mean longevity of male 25.06±0.37 days. These parameters are essential for studying insect ecology and using them in predict programs in the future of the pest and its relationship with its biological enemies.